Long term studies on heavy metals in aquatic organisms from the River Odra mouth area - M. Protasowicki (Acta Ichthyologica et Piscatoria, 1991)
Contents of Hg, Cd, Pb, Cu, and Zn were determined within 1984-1988 in plankton, zebra mussel (Dreissena polymorpha), roach (Rutilus rutilus), bream (Abramis brama), and pikeperch (Lucioperca lucioperca) from different parts of the Rira Odra mouth area. Mercury was determined with CV AAS and assays of the remaining metals were carried out with flame AAS. In terms of their heavy metal contents, the organisms studied can be ordered in the following way: plankton > mussel > fish. A downstream decrease in heavy metal content was observed in the plankton. Mercury contents in fish decreased downstream, too. Mercury, copper, and zinc contents in fish were species-dependent, the highest contents being recorded in roach. Heavy metal dynamics in the plankton over the 5 years of study seems to evidence a gradual reduction in mercury and zinc and an increase in cadmium and lead. However, the changes were not reflected in contents of the metals in fish. No definite trend could be revealed in Hg, Cd, Pb, Cu, and Zn dynamics in roach, bream, and pikeperch, nor a clear-cut pattern could be found with respect to the author′s results published earlier.